James Tobin - Dimand, Robert W. (Great Thinkers in Economics Series, 2014)
James Tobin, 1981 Nobel laureate in economics, was the outstanding monetary economist among American Keynesian economists. This book, the first written about James Tobin, examines his leading role as a Keynesian macroeconomist and monetary economist, and considers the continuing relevance of his ideas.